The overriding driver dynamics in Ethiopia–South Africa migrations - Bereka, Ephrem Zerga; Tufa, Fekadu (Open Science Journal, 2024)
Ethiopian youths and adults have been migrating from South Ethiopia to the Republic of South Africa for the last 40 years. Related studies on sub-Saharan Africa and particularly on Ethiopia have mostly emphasized the combined relationships of the two end drivers of push and pull but have failed to longitudinally examine the migratory experiences and driver dynamics. The two stated end drivers have also been incorporated within the purview of natural, political, and econometric domains, further obscuring overriding factorial reproduction and its changing aspects, which this study elucidated. The present investigation addressed the migration experiences of the Hadiyya and Kambaata ethnic groups and contextually probed how their migration practices shifted from the micro to macro geospatial levels. It also took into account discrete periods, intervening variables, and other changes that have shaped and reshaped the migration patterns and trends of these communities. This study applied a concurrent longitudinal study design via a multisided ethnographic approach. Qualitative semi-structured and unstructured interviews were conducted with one hundred and eight (108) respondents, and observations along with twelve (12) focus group discussions and, ten (10) in-depth interviews were carried out. The study was conducted from June 2016 to January 2019 in two selected rural woredas of the Hadiyya and Kambaata zones in Southern Ethiopia. It also encompassed the downtown locations of Johannesburg and Pretoria, where most Ethiopian migrants reside. In so doing, the study sought to answer two key research questions: how and why the practice of emigration has emerged and transcended beyond the political boundaries of Ethiopia to South Africa and how the migration drivers are evolving. The discussion section of the paper elucidates that migration is not a new phenomenon for these communities; rather, it forms a historical continuum as a culture and a survival strategy to combat resource constraints. However, migration has been galvanized by the combined effects of poverty, political oppression, displacement, and structural, sociopolitical, and economic marginalization after the Ethiopian People’s Revolutionary Democratic Front came into power and instituted ethnicity-based regionalism. Migration is sustained by overriding as well as accompanying changes and challenges at local, national, and international levels. These difficulties cannot be measured merely through environmental, sociopolitical, or econometric-based conditions prevailing at specific times and places. Their determination requires factors beyond such time-bound incidences and parameters. This article is designed to generally discuss and illuminate such comprehensive experiences.